2012
DOI: 10.1097/iae.0b013e318240a529
|View full text |Cite
|
Sign up to set email alerts
|

Combined Fluorescein Angiography and Spectral-Domain Optical Coherence Tomography Imaging of Classic Choroidal Neovascularization Secondary to Age-Related Macular Degeneration Before and After Intravitreal Ranibizumab Injections

Abstract: A discreet pigment epithelial detachment represents a common associated finding of classic choroidal neovascularization. Our study demonstrated that anti-vascular endothelial growth factor treatment may not only stop the growth of the highly reflective subretinal lesion that colocalize with the classic choroidal neovascularization but also determine its regression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Most eyes with type 2 CNV present a small ‘discrete’ PED associated with the highly reflective subretinal lesions (mainly located beneath the subretinal lesion). Increased thickness of the retina, SRF, cystoid spaces and PED are commonly observed 46. RAP (also called type 3 CNV) is described as small erosion or elevated RPE, a flap sign, or, later, a focal funnel-shaped defect in the RPE, called ‘kissing sign’, accompanied by subretinal and/or intraretinal fluid (figure 8).…”
Section: Introductionmentioning
confidence: 99%
“…Most eyes with type 2 CNV present a small ‘discrete’ PED associated with the highly reflective subretinal lesions (mainly located beneath the subretinal lesion). Increased thickness of the retina, SRF, cystoid spaces and PED are commonly observed 46. RAP (also called type 3 CNV) is described as small erosion or elevated RPE, a flap sign, or, later, a focal funnel-shaped defect in the RPE, called ‘kissing sign’, accompanied by subretinal and/or intraretinal fluid (figure 8).…”
Section: Introductionmentioning
confidence: 99%
“…The correspondence between the CNV and the 'intraretinal dense zones' and the exact correspondence between 'en face' OCT images and angiograms were clearly demonstrated [4].…”
Section: Coscas · Coscasmentioning
confidence: 98%
“…Downloaded by: University of Hong Kong 198.143.53.1 -8/18/2015 12:25:31 AM brane and the RPE towards the subretinal space, associated to the sub-and intraretinal dense area and serous subretinal fluid (SRF) (fig. 7)[4].…”
mentioning
confidence: 98%
“…Stevens and associates 43 similarly reported that the presence of classic CNV increases Histologically, it is expected that type 2 CNV may evolve into subretinal fibrotic lesions (type B). However, Dolz-Marco and associates 44 and Coscas and associates 45 have shown that type 2 CNV lesions treated with intravitreal antiangiogenic therapy may progress to a type 1 CNV fibrovascular pattern. Similarly, in our longitudinal series, we observed two type 2 CNV cases and 1 mixed CNV case evolving into subtype A3, and then following the A / B / C pathway.…”
Section: In This Retrospective Study We Described the Cross-mentioning
confidence: 99%